Analysing the desired quality of housing in the Klang Valley region, Malaysia. (4th May 2019) - Yap, Jeffrey Boon Hui; Yong, Pui Si; Skitmore, Martin
ABSTRACT: Housing is crucial for realising the basic requirements of people; it provides a shelter and people spend most of their daily activities in the locality. This study seeks to examine the quality attributes influencing the value of housing and their effect on housing prices according to generation cohorts and affordable housing prices. Twenty-one housing quality factors are first identified by a literature search, with a questionnaire survey ranking safety considerations, air quality, location choice, house ventilation, and accessibility to transportation services to be the highest influence. A further factor analysis reveals five major underlying dimensions of these attributes vis-à-vis locational qualities, values and lifestyles, the availability of public amenities, surrounding environment and product uniqueness, and accessibility. The study's contribution lies in its examination of the housing dimensions affecting quality of life along with providing insights and guidelines for emerging property developers in planning housing development projects in Malaysia and beyond.